جدلية الاتصال والانفصال بين الشرق والغرب، رواية "اللاز" للطاهر وطار - بن حركات, الجمعي (جامعة الوادي - university of Eloued, 2020)
في رواية "اللاز" لـ "الطاهر وطار" التي صدرت سنة 1972، والمؤسسة للجنس الروائي باللغة العربية في الجزائر، نجد علاقة الشرق بالغرب تكتسي طابعا خاصا تحكمه موازين القوة داخل الجزائر، وخارجها (العصر الذهبي للاشتراكية في الجزائر، وانتشار الاشتراكية في العالم على نطاق واسع). فتمثيلات الغرب في هذه الرواية مستمدة أساسا من رؤية الكاتب السياسية والإيديولوجية باعتباره أديبا ثوريا، ومناضلا يساريا يستعمل الأدب وسيلة لنشر الوعي، وهندسة العقول، والقلوب، وتشكيل المخيال الاجتماعي من منطلقات ثقافية معينة. لذلك نجد أن بطل الرواية "زيدان" الذي يعد جسرا عابرا بين الشرق والغرب يمثل هذه المواجهة التي تقوم على جدلية الاتصال، والانفصال؛ الانفصال عن الغرب الاستعماري الرأسمالي، وتفكيكه، والاتصال مع الغرب الشعبي، النضالي، الثوري الذي يمثل الطبقة الشغيلة المناضلة الثائرة، والتي تؤسس للغرب الجديد الذي يدكّ الرأسمالية، والغرب الاستعماري المهيمن. وهذا التواصل تجسده امرأة هي "سوزان" التي يرتبط بها البطل لتفتح له أبواب النجاة، والخلاص، والتجذر في الاشتراكية. فالغرب امرأة عند الروائيين العرب، كما كان الشرق امرأة بالنسبة للرومانسيين الغربيين في القرن التاسع عشر. الغرب امرأة وما يتصل بذلك من استيهامات، ورغبات، وإسقاطات ورموز. ولكن بخلاف كثير من الأدباء العرب الذين وظفوا المرأة الغربية في مخيالهم الروائي، والتي كانت رمزا لاستحالة التواصل الثقافي والحضاري مع الغرب (توفيق الحكيم، سهيل إدريس، الطيب صالح... الخ)، فإن "وطار" وظف المرأة الفرنسية باعتبارها رمزا للحرية، والالتقاء بين الشعوب، والتضامن بين القوى الثورية في العالم، من منطلق الإيديولوجية الأممية، والمصير الإنساني المشترك، إنها خيط "أريان" «fil d’Ariane» الذي ينقذ البطل والشرق والإنسانية. وبخلاف نظرة "كيبلنغ" «Kipling» التشاؤمية، والتي ترى أن الشرق والغرب خطان متوازيان لا يلتقيان أبدا، فإن "الطاهر وطار" يؤسس للالتقاء، والحوار، والتجاوز نحو حلم اشتراكي وطوباوية إنسانية واعدة. Abstract: In the novel "Laz" By: Tahar Ouatar published in 1972, and which established the foundations for the novel genre in Algeria, we find that the relationship of East to West has a special character governed by the balance of power both inside and outside Algeria (the golden age of Socialism in Algeria, and its spread in the world on a large scale) The representations of the West in this novel are primarily derived from the author’s political and ideological vision by telling him a revolutionary writer, and a leftist militant who uses literature to raise awareness, and engineering minds and hearts, and modeling the society imagination from given cultural standpoints. So we find the hero of the novel "Zidene" who is considered a transit bridge between East and West represents this confrontations which stands on connection and separation; separation from the colonial capitalist West and its dismantling, and the connection to the popular revolutionary militant West which represents the labour revolutionary militant class which aims at lying foundations for a new West that will destroy capitalism and the dominant colonial West. Such connection is embodied by a woman named "Suzane" who is associated with the hero to lead him towards survival, salvation and rooting in Socialism. The West is a woman for the Arab novelists as was the East a woman for the western romantisists in the nineteenth century. The West is all inspirations, desires, projections and symbols related to woman. But unlike many Arab writers, who have set up the western woman in their writing imagination as a symbol representing the impossibility of civilization and culture connection with the West (Tawfik El-Hakim, SouhilIdriss, Tayeb Salah …etc.), Ouatar used the French woman as a symbol of liberty, encounter between peoples and solidarity between revolutionary powers in the world. From the standpoint of internationalism ideology and the common human destiny, it is "Arian Thread" which saves the hero, the East and humanity. Unlike "Kipling" pessimistic view which sees East and West as parallel lines which do never meet, TaharOuatar lays foundations for connection, dialogue and transcending towards a socialist dream and a promising human blessedness.
مقال
Keywords: الطاهر؛ وطار؛ رواية؛ اللاز؛ جدلية؛ الشرق؛ الغرب: Tahar, Ouatar, novel, Laz, dialectic, east, west